Microwave‐Assisted Metal‐Free Rapid Synthesis of C4‐Arylated Quinolines via Povarov Type Multicomponent Reaction. Issue 16 (1st April 2019) - Chandra, Devesh; Dhiman, Ankit Kumar; Kumar, Rakesh; Sharma, Upendra
Abstract : A rapid microwave assisted, (±) camphor‐10‐sulfonic acid (CSA) promoted, Povarov type multicomponent synthesis of 4‐arylated quinolines from anilines, alkynes, and paraformaldehyde is described. This reaction proceeds through [4+2] cycloaddition of imine (formed in situ from aniline and paraformaldehyde) and alkynes in the presence of CSA, without any metal catalyst. Mechanistic study revealed that CSA inhibit the synthesis of Troger's base and assist the cycloaddition of imines with alkynes by activating the imine. Abstract : Quinoline Synthesis : Three component reaction of aniline, alkynes, and formaldehyde under microwave irradiation promoted by CSA led to the formation of 4‐arylated quinolines via Povarov type reaction.